2014
DOI: 10.3389/fpls.2014.00621
|View full text |Cite
|
Sign up to set email alerts
|

Conserved cis-regulatory modules in promoters of genes encoding wheat high-molecular-weight glutenin subunits

Abstract: The concentration and composition of the gliadin and glutenin seed storage proteins (SSPs) in wheat flour are the most important determinants of its end-use value. In cereals, the synthesis of SSPs is predominantly regulated at the transcriptional level by a complex network involving at least five cis-elements in gene promoters. The high-molecular-weight glutenin subunits (HMW-GS) are encoded by two tightly linked genes located on the long arms of group 1 chromosomes. Here, we sequenced and annotated the HMW-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(86 citation statements)
references
References 78 publications
4
82
0
Order By: Relevance
“…For the promoter of ONAC026 , SN and NB have an additional stretch of 677 bp, holding multiple copies of DOFCOREZM (AAAG) and EBOXBNNAPA (CANNTG, Figure 3B ), a probable explanation for the higher expression levels in these two accessions ( Figures 2A,D ). EBOXBNNAPA, conserved in many seed storage protein promoters is critical for directing seed-specific expression (Ellerstrom et al, 1996; Ravel et al, 2014), while DOFCOREZM is the recognition core of DOF proteins, reported to activate several storage protein genes (Yamamoto et al, 2006; Abraham et al, 2016). For ONAC023 , the promoter sequences for SN and NB are similar, though there are SNPs amongst the two as well, and hence a similar expression pattern though levels are different.…”
Section: Resultsmentioning
confidence: 99%
“…For the promoter of ONAC026 , SN and NB have an additional stretch of 677 bp, holding multiple copies of DOFCOREZM (AAAG) and EBOXBNNAPA (CANNTG, Figure 3B ), a probable explanation for the higher expression levels in these two accessions ( Figures 2A,D ). EBOXBNNAPA, conserved in many seed storage protein promoters is critical for directing seed-specific expression (Ellerstrom et al, 1996; Ravel et al, 2014), while DOFCOREZM is the recognition core of DOF proteins, reported to activate several storage protein genes (Yamamoto et al, 2006; Abraham et al, 2016). For ONAC023 , the promoter sequences for SN and NB are similar, though there are SNPs amongst the two as well, and hence a similar expression pattern though levels are different.…”
Section: Resultsmentioning
confidence: 99%
“…Five subunits, reported in this study, including the three pairs in the Glu-D t 1, were not detected by the authors. Ribeiro et al (2013) studied the Portuguese wheat Barbela and reported a new x-type HMW-GS encoded at the Glu-A1 locus that was named 1Ax1.1., while Ravel et al (2014) discovered Glu-B1-1 protein 22 in Fruh-weizen (13310) wheat accession. We investigated nine SHW and reported 11 subunits (3 at the Glu-D t 1 locus) as compared to Rasheed et al (2012) analyzing ninety-five Elite-1 synthetic hexaploid wheats (Triticum turgidum/Aegilops tauschii) with 22 glutenins (13 at the Glu-D t 1 locus).…”
Section: Discussionmentioning
confidence: 99%
“…Transformation of endosperm was based on a method described by Ravel and co-workers (Ravel et al 2014) with the modification that 1 g l -1 casein hydrolysate was included in the medium after the transformation, instead of separately adding all the 20 proteinogenic amino acids. Biolistic bombardment of endosperms was carried out identically to the leaves.…”
Section: Transient Reporter Gene Expression Assaymentioning
confidence: 99%
“…Since then the first draft genome of Triticim aestivum has been published (Mayer et al 2014a) and it gave us a new opportunity to improve the experiment by calculating the global overrepresentations of binding sites and binding site clusters. In a parallel study, Ravel et coworkers reported conserved cis-regulatory modules in the promoters of HMW-GS promoters that they identified by a simple and non-statistical method (Ravel et al 2014). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation